2015
DOI: 10.1007/s11010-014-2318-6
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin gene-related peptide stimulates proliferation and osteogenic differentiation of osteoporotic rat-derived bone mesenchymal stem cells

Abstract: Osteoporosis, a systemic bone disorder, is prevalent in postmenopausal woman. Bone mesenchymal stem cells (BMSCs), precursors of osteogenic cells, may contribute to prevention or treatment of bone frustrate in osteoporosis. Recently, two studies suggested a role of calcitonin gene-related peptide (CGRP) in promoting osteogenesis of BMSCs under physiological conditions. However, the role of CGRP on BMSCs, which are derived from osteoporotic tissues, is unclear. Here, we investigated the role of CGRP on BMSCs is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(35 citation statements)
references
References 32 publications
1
32
0
Order By: Relevance
“…But, since we obtained the reverse result (Figure 3 ), we hypothesized that our observations must be due to an indirect systemic effect of AM. A possible mechanism may involve the increase in CGRP shown in Figure 1D , since CGRP can induce bone growth through stimulation of bone mesenchymal stem cells (Liang et al, 2015 ). Also, AM has been shown to reduce insulin secretion in the pancreas, thus increasing glucose levels (Martinez et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…But, since we obtained the reverse result (Figure 3 ), we hypothesized that our observations must be due to an indirect systemic effect of AM. A possible mechanism may involve the increase in CGRP shown in Figure 1D , since CGRP can induce bone growth through stimulation of bone mesenchymal stem cells (Liang et al, 2015 ). Also, AM has been shown to reduce insulin secretion in the pancreas, thus increasing glucose levels (Martinez et al, 1996 ).…”
Section: Resultsmentioning
confidence: 99%
“…A number of previous reports have focused on the effects of CGRP on cultured osteoblasts and have revealed that CGRP can regulate bone metabolism and stimulate osteoblasts differentiation (17,30,31). Nevertheless, only a few reports have reported on LPS-induced osteoblast apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP participates in the regulation of growth, repair and performance Effects of a novel CGRP-Sr-CPC on osteoporotic rat-derived BMSCs e438 of bone by working on BMSCs (40)(41)(42). Our recent study discovered positive effects of CGRP in stimulation of cell growth and induction of osteogenic differentiation in BMSCs derived from osteoporosis (11). Based on the promising effects of CGRP on BMSCs, we created CGRP-CPC.…”
Section: Discussionmentioning
confidence: 99%